Jupiter's Double‐Arc Aurora as a Signature of Magnetic Reconnection: Simultaneous Observations From HST and Juno. Issue 14 (28th July 2021) - Guo, R. L.; Yao, Z. H.; Grodent, D.; Bonfond, B.; Clark, G.; Dunn, W. R.; Palmaerts, B.; Mauk, B. H.; Vogt, M. F.; Shi, Q. Q.; Wei, Y.; Connerney, J. E. P.; et al.
Abstract: Jupiter's powerful auroral emission is usually divided into the polar, main, and equatorward components. The driver of Jupiter's main aurora is a central question for the community. Previous investigations reveal many distinct substructures on the main auroral oval, which are indicators of fundamentally different magnetospheric processes. Understanding these substructures could provide key constraints for uncovering the driver of Jupiter's main aurora emission. In this study, we show the evolution of a double‐auroral arc on the dawnside from observations by the Hubble Space Telescope (HST). Simultaneous in situ observations from the Juno spacecraft provide direct evidence of magnetic reconnection and magnetic dipolarization. By analyzing the datasets from Juno and HST, we suggest that the evolution of the double‐arc structure is likely a consequence of the non‐steady progress of magnetic reconnection. Plain Language Summary: Jupiter's most powerful aurora reflects the strong perturbations of energetic particles in the space environment. Besides the relatively steady main aurora, there are rapidly evolving structures that imply the transient plasma processes, for example, magnetic reconnection, wave‐particle interaction, and so on. The relation between transient processes and auroral structures is poorly understood due to limited observations. Using the simultaneous measures from Juno and Hubble Space Telescope, we reveal the magnetospheric driver (i.e., magnetic reconnection) for an evolving double‐arc auroral structure at the dawn sector. This study shows a good example of reconnection signature on the auroral image, which provides key implications to understand planetary space environment from dynamic auroral features. Key Points: We investigate a double‐arc dawn aurora at Jupiter and the associated reconnection signatures in magnetosphere for the poleward arc Poleward arc evolves rapidly and both arcs move equatorward, suggesting a combination of global reconfiguration and localized reconnection Multiple reconnection fronts observed by Juno are suggestive evidence of unsteady and/or drizzle‐like reconnection processes